More than a thank you note : academic library fundraising for the dean or director - Thompson, Kimberly A.; Jennings, Karlene Noel.; ScienceDirect eBooks (Witney : Chandos Publishing (Oxford) Ltd, 2009)
This book provides friendly, lively discussion of the role of the academic library fund-raising written by two experienced library fund-raisers.
You as the fundraiser -- Your fundraiser -- Your library staff -- Your special collections (and other unique features) -- Your Friends of the Library -- Your advisory council -- Your library patrons -- Your central development team and other development officers -- Your campus community -- Your administration -- Your community -- Your donors are unique -- You and crisis management -- What your fundraiser wants you to know -- Conclusion: Putting it all together.
Includes bibliographical references (page 197) and index.
Elsevier
Keywords: Academic libraries -- Finance; Library fund raising; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Academic libraries -- Finance; Library fund raising; Electronic books